Low level laser therapy for the management of breast cancer‐related lymphedema: A randomized controlled feasibility study. Issue 9 (30th May 2018) - Baxter, George David; Liu, Lizhou; Tumilty, Steve; Petrich, Simone; Chapple, Cathy; Anders, Juanita J.; ,
Abstract : Objectives: This study aimed to determine the feasibility of conducting a full scale randomized controlled trial investigating the effectiveness of low level laser therapy (LLLT), also known as photobiomodulation (PBM) therapy, used in addition to conventional therapy, for managing breast cancer related lymphedema (BCRL). Materials and Methods: Patients with BCRL were recruited from the Southern District Health Board (New Zealand) via lymphedema therapists' referrals, and randomly allocated into either the laser group, which received BCRL conventional therapy (e.g., wearing compression garments, massage therapy, and/or exercise) plus a 6‐week LLLT (PBM) intervention program (wavelength: 980/810 nm (80:20 ratio); output power: 500 mW beam spot size: 5 cm 2 ; irradiance: 100 mW/cm 2 ; treatment time per area: 1 minute dosage per area treated: 30J (6J/cm 2 ); 10 points of treatment from axilla to wrist total LLLT (PBM) treatment time: 10 minutes total dosage delivered: 300 J), or the control group, which received BCRL conventional therapy alone. Feasibility was determined by recruitment and randomization rates, retention of participants and treatment protocol adherence, and was assessed during the recruiting and intervention periods. Data on participant satisfaction and adverse reactions of LLLT (PBM) were collected on completion of this study. Clinical outcomes (i.e., limb circumference, participant's perceived symptoms, psychological impacts, and activity disability) were assessed at baseline, and 6 and 12 weeks post‐randomization. Results: Over a 6‐month recruitment window, 17 participants with BCRL were recruited in the study, and randomized into the two groups (recruitment rate of 81%, and randomization rate of 100%). Treatment adherence was high in the laser group (88.9% of participants completed all treatments). Retention rates were 88.9% for the laser group and 100% for the control group at both 6 and 12 weeks post‐randomization. All participants who completed LLLT (PBM) treatment indicated that they were satisfied with the treatment. No serious adverse reactions were reported in this study. Clinical outcomes failed to show additional benefits of LLLT (PBM) intervention. Conclusion: This study demonstrated that it is feasible to conduct a fully powered RCT to definitively test the effectiveness of the additional use of LLLT (PBM) in the management of BCRL. For such a trial, 114 participants will be needed at baseline. Lasers Surg. Med. 50:924–932, 2018. © 2018 Wiley Periodicals, Inc.